2020
DOI: 10.1186/s12913-020-05684-7
|View full text |Cite
|
Sign up to set email alerts
|

How does GP training impact rural and remote underserved communities? Exploring community and professional perceptions

Abstract: Background Substantial government funding has been invested to support the training of General Practitioners (GPs) in Australia to serve rural communities. However, there is little data on the impact of this expanded training on smaller communities, particularly for smaller rural and more remote communities. Improved understanding of the impact of training on underserved communities will assist in addressing this gap and inform ongoing investment by governments and communities. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This is thought to be particularly so in rural and remote communities where, often, populations are older and GP workforce more thinly distributed. 14,15 In an earlier study of Australian earlycareer specialist GPs, associations of provision of NHVs and HVs with rurality were not significant. 1 We aimed to examine the NHV and HV practice of early-career specialist GPs.…”
Section: What Is Already Known On This Subject?mentioning
confidence: 92%
See 1 more Smart Citation
“…This is thought to be particularly so in rural and remote communities where, often, populations are older and GP workforce more thinly distributed. 14,15 In an earlier study of Australian earlycareer specialist GPs, associations of provision of NHVs and HVs with rurality were not significant. 1 We aimed to examine the NHV and HV practice of early-career specialist GPs.…”
Section: What Is Already Known On This Subject?mentioning
confidence: 92%
“…An understanding of the current practice patterns of early‐career GPs is essential in planning for future community NHV and HV provision. This is thought to be particularly so in rural and remote communities where, often, populations are older and GP workforce more thinly distributed 14,15 . In an earlier study of Australian early‐career specialist GPs, associations of provision of NHVs and HVs with rurality were not significant 1 .…”
Section: Introductionmentioning
confidence: 98%
“…Concerning the actual status in China, it is imperative to explore an effective GP training model, improve the sub-specialty ability of GPs, and cultivate GPs with a special interest [21][22][23][24][25][26] .…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…General practice training is provided in geographically diverse locations across Australia to promote the development of the rural and remote medical workforce. Training in rural and remote locations supports learning locally required types of medical practice and builds both social and professional connections that increase the likelihood of trainees later practising in these communities 1,2 . The remote learning model appears to be successful, 3 but a 2020 scoping review found only limited evidence for the equivalence of learning outcomes after training in remote or less remote locations 4 .…”
mentioning
confidence: 99%